2013
DOI: 10.1111/1758-2229.12059
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis in the pathogenesis of Nosema ceranae (Microsporidia: Nosematidae) in honey bees (Apis mellifera)

Abstract: Nosema ceranae is a parasite of the epithelial ventricular cells of the honey bee that belongs to the microsporidian phylum, a biological group of single-cell, spore-forming obligate intracellular parasites found in all major animal lineages. The ability of host cells to accommodate a large parasitic burden for several days suggests that these parasites subvert the normal host cells to ensure optimal environmental conditions for growth and development. Once infected, cells can counteract the invasive pathogen … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
48
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 38 publications
3
48
1
1
Order By: Relevance
“…mellificae was significantly higher than that of those that received C. mellificae alone and that of the control worker bees (Kaplan-Meier Long-Rank test, p<0.001). Conversely, the survival of the control and the C. mellificae infected bees was significantly higher than that of the references tion with N. ceranae is consistent with that seen previously (reviewed by Higes et al, 2013;Williams et al, 2014;Huang et al, 2015;Milbrath et al, 2015), confirming that bees infected with N. ceranae have a shorter life expectancy than uninfected bees. The incubation temperature used may explain the distinct evolution in the survival of infected honey bees relative to other laboratory experiments performed in our laboratory (Martín-Hernandez et al, 2009).…”
Section: Resultssupporting
confidence: 91%
See 4 more Smart Citations
“…mellificae was significantly higher than that of those that received C. mellificae alone and that of the control worker bees (Kaplan-Meier Long-Rank test, p<0.001). Conversely, the survival of the control and the C. mellificae infected bees was significantly higher than that of the references tion with N. ceranae is consistent with that seen previously (reviewed by Higes et al, 2013;Williams et al, 2014;Huang et al, 2015;Milbrath et al, 2015), confirming that bees infected with N. ceranae have a shorter life expectancy than uninfected bees. The incubation temperature used may explain the distinct evolution in the survival of infected honey bees relative to other laboratory experiments performed in our laboratory (Martín-Hernandez et al, 2009).…”
Section: Resultssupporting
confidence: 91%
“…The DNA from those colonies was extracted as described previously in Cepero et al (2014) and the trypanosomatid species was confirmed by PCR (Meeus et al, 2010) and subsequent sequencing (Cepero et al, 2014). Freshly purified N. ceranae spores for experimental infection were obtained as described elsewhere (Martín-Hernández et al, 2011Higes et al, 2013), counting both the N. ceranae spores and C. mellificae spheroid forms in a haemocytometer. DNA was extracted from an aliquot of Nosema spores to confirm the species by PCR (Martín-Hernández et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations